Hungarian Monitoring, 8 October 1988 . [Magyar rádiófigyelő], 1988. október 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Further Iranian weapons transports scandals to come? - On turmoil in Algeria - Estonian popular front congress - Rakowski gives speech to factory directors Domestic Affairs: - Szeged Party committee first secretary emphasizes at town Party assembly the need to change leaders who discredit the Party - More recent criticisms of Young Communist League (KISZ) and its leaders - Rezső Nyers does not have faith in Gabčíkovo-Nagymaros project - Hungarian peace council and other peace groups recommend that alternative military service be made possible from January - Demonstrations start to become more and more common: deputy interior minister on how many protests have taken place and how the police prepare for them - Olympic doping scandal - Film on the 1948 violence against Catholics in Pócspetri finally out of the box Economy: - Károly Grósz receives managing director of transportation giant TNT - Conversation with the Hungarian Chamber of Commerce general secretary Külpolitika: - Újabb iráni fegyverszállítási botrány a levegőben? - Az algériai lázongásokról - Az észt népfront kongresszusa - Rakowski gyárigazgatók előtt tartott beszéde Belpolitika: - A pártot lejárató vezetőktől feltétlenül meg kell válni - Hangsúlyozta a szegedi pártbizottság első titkára a városi pártértekezleten - Sok bírálat érte az utóbbi időben a KISZ-t és vezetőit - Nyers Rezső nem bízik a bős-nagymarosi beruházásban - A magyar béketanács és más hazai békecsoport javasolja, hogy januártól tegyék lehetővé az alternatív katonai szolgálatot - Lassan megszokott jelenséggé válnak a tüntetések - A belügymin-helyettes elmondja hány volt eddig, és hogyan készül fel erre a rendőrség - Olimpiai doppingbotrány - Kikerült végre a dobozból a Pócspetri-ügyet feldolgozó film Gazdaság: - Grósz Károly fogadta a TNT közlekedési óriásvállalat vezérigazgatóját - Beszélgetés a Magyar Gazdasági Kamara főtitkárával